Menggagas Konsep Pelindungan Pekerja Rumah Tangga Migran Perempuan oleh Negara dalam Perspektif Islam - Nur Maulidia; Siti Afifah Khumairoh; Syafrida Aulianur Rarasatti (Fakultas Hukum Universitas Islam Indonesia, 2025)
The low number of job vacancies in Indonesia is inversely proportional to the large population, so the government has made efforts to solve this problem by sending Indonesian Migrant Workers abroad, one of which is Saudi Arabia. However, over time, many complaints from migrant workers related to the violence they received while working. To overcome this, the perspective of Islamic law is used because Saudi Arabia formally applies Islamic law. This research formulates two main problems: what is the status of female migrant domestic workers in the perspective of Islamic law, and what is the concept of protection by the state according to Islamic views. The method used is normative juridical research with secondary data in the form of primary and secondary legal materials through document and literature studies. The results of the study show that, first, Islam recognizes women's right to work as long as they maintain the values of sharia and safety. Second, in Islam, the state as a trustee (al-imāmah) is obliged to protect female migrant domestic workers.